The Effect of E-Service Quality on Repurchase Intention of KAI Access Users with Customer Satisfaction as an Intervening Variable - Navira Wirvani; Maya Ariyanti (International Journal of Economics, Business and Innovation Research, 2024)
The post-pandemic surge in mobility has increased demand for transportation services, particularly trains. The development of the KAI Access digital platform contributes to this growth by offering ticket booking and trip planning features that improve user experience. Despite this, service quality still needs to be improved, especially booking problems and system errors that users often report. This study aims to investigate the relationship between KAI Access e-service quality and user repurchase intentions, with customer satisfaction as a mediator. This quantitative research involved 274 respondents selected through purposive sampling method, and analyzed using Structural Equation Modeling (SEM) method with SmartPLS 3 application. The results showed that electronic service quality has a positive and significant influence on customer satisfaction and repurchase intention, both directly and through customer satisfaction and customer satisfaction also has a positive effect on repurchase intention. These findings are expected to provide insight for PT Kereta Api Indonesia to improve the performance of the KAI Access application by focusing on improving the quality of electronic services to increase repurchase intention through increased customer satisfaction.